Design and contruction of a loop-quad antenna for use at C-Band / Maslina Al-Ahmady Mohd Amin - Mohd Amin, Maslina Al-Ahmady (1996)
In this thesis, the design and construction of a loop-quad antenna is described. The design is aided by a software written in Turbo Pascal. The radiation pattern was simulated using MAPLE V Mathematical Package. A simple simulation was attempted based on constant current approximation in the loop. Basically, the gain of loop antenna is very low and this was improved by incorporating parasitic elements acting as directors. A 27 element loop-quad antenna was designed and constructed. The gain is about 18.8 dB and this is nearly expected gain which is 20 dB[l]. The SWR is between frequency of 3.61GHz and 4.41GHz. The radiation pattern gives a beamwidth of 22.4 degrees and the efficiency of 26.37%.